Design thinking : a guide to innovation - Estes, Fred, 1950- (Twenty-First Century Books, 2025)
"Design thinking is a six-step process used in creative problem solving to understand users, challenge assumptions, redefine problems, and create innovative solutions. As a human-centered approach to innovation, design thinking is used in everything from corporate structure in businesses such as UberEATS, AirBnB, and Adobe XD to local and regional projects. Design Thinking by author and educator Fred Estes provides a simple, clear approach to the six-step design thinking process. This easy-to-follow guide explains everything essential to design thinking projects focused on solving human-centered, social issues. Readers will learn the fundamentals of each of the six steps in the design thinking model- notice and reflect, empathize, define, ideate, prototype, and test- and discover how to collaborate with people to develop solutions to real-world problems and create better communities through creativity, inspiration, and teamwork. With true stories of real student teams and their projects, this book provides readers with the steps to effect change and create a more equitable world." --